2022
DOI: 10.1186/s12969-022-00673-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary antiphospholipid syndrome in pediatrics: beyond thrombosis. Report of 32 cases and review of the evidence

Abstract: Objective Describe the frequency of thrombotic and non-thrombotic clinical manifestations, laboratory, treatment and prognosis in patients with pediatric primary antiphospholipid syndrome. Material and methods A retrospective study was carried out in patients with a diagnosis of primary antiphospholipid antibody syndrome, under 16 years of age, under follow-up by the pediatric rheumatology service of the General Hospital, National Medical Center, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Pediatric APS, specifically diagnosed in individuals under the age of 18 years, typically manifests between nine and 14 years of age [ 9 , 10 ]. Furthermore, it is estimated that up to 24-50% of APS cases in children are classified as primary [ 11 ]. As of now, there are no specific criteria established for the diagnosis of APS in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric APS, specifically diagnosed in individuals under the age of 18 years, typically manifests between nine and 14 years of age [ 9 , 10 ]. Furthermore, it is estimated that up to 24-50% of APS cases in children are classified as primary [ 11 ]. As of now, there are no specific criteria established for the diagnosis of APS in children.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thrombosis is a prevalent occurrence, affecting approximately 60% of cases. However, arterial thrombosis (most commonly presented as ischemic cardiovascular disease) and small vessel thrombosis may also be present [ 10 , 11 ]. Skin-related symptoms include livedo reticularis, Raynaud's phenomenon, skin ulcers, and pseudo-vasculitic lesions [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that in comparison to adult patients with NC-aPL or conventional aPL, thrombosis is less likely to be a frequent manifestation in pediatric patients [ 31 ]. Studies of developmental hemostasis have demonstrated that the levels of many procoagulant factors (FII, FV, FVII) increase throughout childhood and more so into adolescence after puberty [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%